已知5a^2+4ab+b^2-6a+9=0,求a+b
1个回答
原式可化为
a2+4a2+4ab+b2-6a+9=0
即(a2-6a+9)+(4a2+4ab+b2)=0
(a-3)2+(2a+b)2=0
所以a-3=0,2a+b=0
a=3,b=-6
a+b=-3
相关问题
已知a^2-4a+9b^2+6b+5=0,求a^2-6ab+9b^2的值
已知a^2+9b^2+4a-6b+5=0,求代数式a+3b/a+2b除以a^2+6ab+9b^2/a^2-4b^2
已知a2+4a+9b2+6b+5=0,求a,b的值.
已知a^2-4a+9b^2+6b+5=0求a+b的值
已知a2+4a+9b2+6b+5=0,求a,b的值.
已知a-4的绝对值+根号6-9=0,求(a^2+ab/b^2)/(a^2-ab/a^2-b^2)
(a²+ab)÷(a²-b²)=?2.已知a²-4a+9b²+6b+5
(2010•石景山区二模)已知:4a2+b2=4ab(ab≠0),求[a−b/a+3b÷a2−b2a2+6ab+9b2−
已知9a^2-4b^2=0,求代数式a/b-b/a-(a^2+b^2/ab)
已知a²+2ab+2b²-6b+9=0,求a-b的值